2009
DOI: 10.1002/ibd.20927
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal healing predicts long-term outcome of maintenance therapy with infliximab in Crohnʼs disease

Abstract: MH induced by long-term maintenance IFX treatment is associated with an improved long-term outcome of the disease especially with a lower need for major abdominal surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
356
0
16

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 614 publications
(380 citation statements)
references
References 18 publications
8
356
0
16
Order By: Relevance
“…As many patients with IBD were either refractory or intolerant to treat ment with the classic agents already discussed, there was an urgent need for the development of more specific novel therapeutic approaches. In this context, anti TNF agents, including infliximab, adalimumab, golimumab and certo lizumab pegol, were introduced into clin ical therapy for IBD 14,[23][24][25][26][27][28][29][30][31][32][33] . For instance, infliximab was shown to be effective for induction and maintenance of remission in both Crohn's disease and ulcerative colitis as well as for treatment of fistulas in Crohn's disease, highlighting the broad relevance of anti TNF therapy 14,24 .…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…As many patients with IBD were either refractory or intolerant to treat ment with the classic agents already discussed, there was an urgent need for the development of more specific novel therapeutic approaches. In this context, anti TNF agents, including infliximab, adalimumab, golimumab and certo lizumab pegol, were introduced into clin ical therapy for IBD 14,[23][24][25][26][27][28][29][30][31][32][33] . For instance, infliximab was shown to be effective for induction and maintenance of remission in both Crohn's disease and ulcerative colitis as well as for treatment of fistulas in Crohn's disease, highlighting the broad relevance of anti TNF therapy 14,24 .…”
Section: Classic Immunosuppressive Drugsmentioning
confidence: 99%
“…Mucosal healing is likely to become an important therapeutic target in CD, being associated with sustained clinical remission, and reduced rates of hospitalization and surgery [46][47][48][49]. Anti-tumour necrosis factor (TNF) a agents are effective in the treatment of Crohn's disease CD because they can induce clinical remission and mucosal healing in most patients.…”
Section: Sicusmentioning
confidence: 99%
“…The distinction between these two grades is, therefore, not clinically relevant and current postoperative therapeutic strategies are aimed at aggressively treating only severe endoscopic recurrence. Similarly, in a retrospective study on a large cohort of CD patients treated with infliximab, no difference in the long-term need of major abdominal surgery was observed in patients who achieved complete MH (absence of ulcerations) or partial MH (clear improvement of mucosal lesions, but still with ulcerations) [4]. In UC, a substudy of the ACT 1 and ACT 2 trials showed that early MH with infliximab was associated with a reduced risk of colectomy within 1 year, but the colectomy-free survival was similar in patients who achieved complete MH (Mayo score = 0) or partial MH (Mayo score = 1) [8].…”
mentioning
confidence: 89%
“…IBD encompasses a wide range of endoscopic lesions, but there is no current standardized definition of MH and several criteria have been arbitrarily used. In CD, MH has been defined either in a simple and pragmatic manner as 'absence of ulcerations at follow-up endoscopy in patients who had ulcerations at baseline' [4] or using endoscopic scores, such as the CD endoscopic index of severity or the simple endoscopic score for CD (SES-CD) [5]. Unfortunately, these scores were initially KEYWORDS: Crohn's disease • endoscopy • inflammatory bowel disease • mucosal healing • ulcerative colitis informahealthcare.comconceived as continuous-variable systems and no agreement on cut-off values to define MH exist.…”
mentioning
confidence: 99%